The Para-Academic Handbook A Toolkit for Making-Learning-Creating-Acting - Wardrop, Alex; Withers, Deborah (Intellect, 2014)
"There is a name for those under-and precariously employed, but actively working, academics in today's society: the para-academic. Para-academics mimic academic practices so they are liberated from the confines of the university. Our work, and our lives, reflect how the idea of a university as a place for knowledge production, discussion and learning, has become distorted by neo-liberal market forces. We create alternative, genuinely open access, learning-thinking-making-acting spaces on the internet, in publications, in exhibitions, discussion groups or other mediums that seem appropriate to the situation. We don't sit back and worry about our career developments paths. We write for the love of it, we think because we have to, we do it because we care."